Cephalometric norms and esthetic profile preference for the Japanese: a systematic review - Caroline Nemetz Bronfman; Guilherme Janson; Arnaldo Pinzan; Thais Lima Rocha (Dental Press Editora, 2015)
Abstract Objective: To determine the cephalometric parameters and esthetic preferences of a pleasant face for the Japanese population. Methods: For the present study, the following databases were accessed: PubMed, Embase, Scopus and Web of Science. Initial inclusion criteria comprised studies written in English and quoting cephalometric norms and/or facial attractiveness in Japanese adults. No time period of publication was determined. The quality features evaluated were sample description, variables analyzed and how cephalometric standards or facial profile were evaluated. Results: Initially, 60 articles were retrieved. From the selected studies, 13 abstracts met the initial inclusion criteria. They were divided into two groups; seven articles were included in Group I and six articles in Group II, according to the criteria of evaluation: cephalometric or facial analyses. Conclusion: Japanese are characterized by having a less convex skeletal profile, bilabial protrusion, less prominent nose, more retruded chin and protruded mandibular incisor. Despite living in a society with homogeneous patterns, they seem to get an esthetic preference for white-like features. Therefore, in addition to ethnic normative values, patient's preferences to establish individual treatment plans should always be considered.